SAT0010 Common epitope structure of HLA-DPB1 in systemic sclerosis. (23rd January 2014) - Lee, J.; Kim, H.J.; Lee, H.K.; Park, J.A.; Kim, H.W.; Song, Y.W.; Lee, E.B.
Abstract : Background: Specific alleles of HLA-DPB1 (HLA-DPB1*0901, *1301, *0301) were found to be most strongly associated with anti-topoisomerase I (Topo-I)-positive systemic sclerosis (SSc) in multiethnic genome-wide association study and HLA-analysis (1, 2). However, structural basis on which HLA-DPB1 alleles can bind Topo-I peptides is unknown. Objectives: To find common characteristics of amino acid sequences in the risk HLA-DPB1 alleles and to reveal the possible mode of binding with Topo-I. Methods: We enrolled 127 Korean patients with SSc who were diagnosed as SSc according to the preliminary classification criteria of American College of Rheumatology and 548 healthy Korean controls. We compared amino acid sequences of the risk HLA-DPB1 alleles with non-risk alleles, focusing on known HLA-DP binding motifs. After revealing common peptides from risk alleles of HLA-DPB1, molecular dynamic simulation was conducted to show binding structures against hypothetically chosen sequences of amino acids in Topo-I. Results: The triplet of negative charged amino acids in three critical sites were associated with SSc. At amino acid position 55-57, 67-69, and 82, 84-85 of HLA-DPB1, negatively charged amino acids were prevalent, which includes glutamine or lysine. The patients who have 3 negative charged triplets show OR of 5.99 (95% CI=2.17-16.6, p=1.8×10 -4 ) for SSc and those who have 2 negative charged triplets show OR of 6.37 (95% CI=2.35-17.3, p=7.1×10 -5 ) or 3.89 (95% CI=1.39-10.9, p=6.5×10 -3 ), while those who do not have triplets have referent OR of 1.00. When peptides from Topo-I (peptide A (KDR EHR HK EHK K) and peptide B (KLL KEY GF CIM D)) were selected to simulate interaction with "high risk" HLA-DP allele (HLA-DPB1*0901) and "low risk" allele (HLA-DPB1*040101), peptide A and B fit more closely into the binding cleft of HLA-DPB1*0901 than HLA-DPB1*040101. (Figure 1 ) Conclusions: SSc-susceptible HLA-DPB1 alleles share negative charged amino acid triplets at critical positions in their peptide binding groove. References: Zhou, X., et al., Arthritis Rheum, 2009. 60(12): p. 3807-14. Arnett, F.C., et al., Ann Rheum Dis, 2010. 69(5): p. 822-7. Disclosure of Interest: None Declared